Relationship between complex means-end and types of coping to economic crisis - Vicuña Peri, Luis A. (2000)
The present investigation has as intention to know the existent relationship among the complex means end (Adler,A) with the types of it confronts before the economic crisis, studied from the perspective of the theory of the atributions according to Peterson and Villanova. We want to explore if the productive orientation of the personality is related with the style optimistic atribucional. Likewise we have analyzed the paper that plays the labor condition and the gender in the mentioned correlation. We have worked with a constituted aleatory sample OR 483 subject of Lima, representative at the 0.05 of error margin to who you/they were applied two worth questionnaires and reliable, the first one was the Monofactorial of lifestyles and the second was the ASQ-CIDE, of styles attributions. Making the analysis you concludes that there is correlation inverse negative among the. productive personality with the style optimistic atribucional it is significant bigger regarding the group of unemployed. For another art the contrastación of correlations made in function to the I generate he/she tells us that est year is a variable that affects in significant stocking to the correlations. In summary we can affirm that the productive orientation and the style optimistic atribucional are characteristic in those subject with employment what takes to outline in next studies if the type of personality and the style atribucional influence about the success in getting or to generate their own employment, beca use the present study doesn't open the possibility correlacional that is this way.